Implementation of gray level CO - occurrence matrix on embedded system - Lau,Iris Jia Wen, 1990-, author; Zaid Omar, supervisor; Fakulti Kejuruteraan Elektrik (2014)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) ) - Universiti Teknologi Malaysia, 2014